2020
DOI: 10.1111/gcb.15299
|View full text |Cite
|
Sign up to set email alerts
|

Plant biomes demonstrate that landscape resilience today is the lowest it has been since end‐Pleistocene megafaunal extinctions

Abstract: Resilient landscapes have helped maintain terrestrial biodiversity during periods of climatic and environmental change. Identifying the tempo and mode of landscape transitions and the drivers of landscape resilience is critical to maintaining natural systems and preserving biodiversity given today's rapid climate and land use changes. However, resilient landscapes are difficult to recognize on short time scales, as perturbations are challenging to quantify and ecosystem transitions are rare. Here we analyze tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 89 publications
(150 reference statements)
0
19
0
Order By: Relevance
“…Concurrently, in eastern North America, rates of habitat reorganization were high (Wang et al., 2020), and open conifer and mixed conifer–hardwood parklands were lost, replaced by a Holocene arrangement of grasslands and eastern mesic forests (Williams et al., 2004). These losses of Pleistocene open parklands may have reduced the habitat availability for megafaunal species (Blois & Hadly, 2009; Di Febbraro et al., 2017; Ficcarelli et al., 2003; Graham, 1986; Haynes, 2013), increased competition among megafauna species, and thus increased the extinction risk of the woolly mammoth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, in eastern North America, rates of habitat reorganization were high (Wang et al., 2020), and open conifer and mixed conifer–hardwood parklands were lost, replaced by a Holocene arrangement of grasslands and eastern mesic forests (Williams et al., 2004). These losses of Pleistocene open parklands may have reduced the habitat availability for megafaunal species (Blois & Hadly, 2009; Di Febbraro et al., 2017; Ficcarelli et al., 2003; Graham, 1986; Haynes, 2013), increased competition among megafauna species, and thus increased the extinction risk of the woolly mammoth.…”
Section: Discussionmentioning
confidence: 99%
“…This observed afforestation is partially attributable to rising temperatures (Fastovich et al., 2020) but may also indicate that woolly mammoths, as ecosystem engineers, played important roles in landscape transformation. These landscape transitions may also have acted as a positive feedback loop of habitat loss (Wang et al., 2020) that exacerbated the woolly mammoth population decline and extinction. A next step forward is to include megaherbivory in mechanistic dynamic vegetation models such as LPJ‐GUESS; such models are at the early stages of development (Pachzelt et al., 2013, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of lake‐sediment pollen cores corresponding to the last 20,000 years of North American ecological history showed that ecosystems persisted for an average of just 230–460 years before transitioning to another ecosystem type (Wang, Shipley, Lauer, Pineau, & McGuire, 2020). Sixty‐four percent of these systems eventually reverted to their previous ecosystem type, but the rest did not.…”
Section: Ways To Conceptualize Integritymentioning
confidence: 99%
“…Sixty‐four percent of these systems eventually reverted to their previous ecosystem type, but the rest did not. In particular, Pleistocene megafaunal extinctions “led to rapid changes where plant communities transitioned through multiple alternative states rapidly” (Wang et al, 2020, p. 5,923).…”
Section: Ways To Conceptualize Integritymentioning
confidence: 99%